Transgenerational epigenetic inheritance in plants - Hauser, Marie-Theres (Biochim Biophys Acta, 2011)
Interest in transgenerational epigenetic inheritance has intensified with the boosting of knowledge on epigenetic mechanisms regulating gene expression during development and in response to internal and external signals such as biotic and abiotic stresses. Starting with an historical background of scantily documented anecdotes and their consequences, we recapitulate the information gathered during the last 60 years on naturally occurring and induced epialleles and paramutations in plants. We present the major players of epigenetic regulation and their importance in controlling stress responses. The effect of diverse stressors on the epigenetic status and its transgenerational inheritance is summarized from a mechanistic viewpoint. The consequences of transgenerational epigenetic inheritance are presented, focusing on the knowledge about its stability, and in relation to genetically fixed mutations, recombination, and genomic rearrangement. We conclude with an outlook on the importance of transgenerational inheritance for adaptation to changing environments and for practical applications. This article is part of a Special Issue entitled “Epigenetic control of cellular and developmental processes in plants”.